2011
DOI: 10.1542/peds.2010-3507
|View full text |Cite
|
Sign up to set email alerts
|

NIH Consensus Development Conference Statement: Inhaled Nitric-Oxide Therapy for Premature Infants

Abstract: Premature birth is a major public health problem in the United States and internationally. Infants born at or before 32 weeks' gestation (2% of all births in the United States in 2007) are at extremely high risk for death in the neonatal period or for pulmonary, visual, and neurodevelopmental morbidities with lifelong consequences including bronchopulmonary dysplasia, retinopathy of prematurity, and brain injury. Risks for adverse outcomes increase with decreasing gestational age. The economic costs to care fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(174 citation statements)
references
References 0 publications
5
161
2
3
Order By: Relevance
“…After reviewing the published evidence, the panel concluded that the available evidence does not support the use of iNO in early routine, early rescue, or later rescue regimens in the care of infants born at less than 34 weeks' gestation and that hospitals, clinicians, and the pharmaceutical industry should avoid marketing iNO for this group of infants. 8 An individual-patient data meta-analysis of 14 randomized controlled trials reached similar conclusions. 9 The purpose of this clinical report is to summarize the existing evidence for the use of iNO in preterm infants and provide guidance regarding its use in this population.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…After reviewing the published evidence, the panel concluded that the available evidence does not support the use of iNO in early routine, early rescue, or later rescue regimens in the care of infants born at less than 34 weeks' gestation and that hospitals, clinicians, and the pharmaceutical industry should avoid marketing iNO for this group of infants. 8 An individual-patient data meta-analysis of 14 randomized controlled trials reached similar conclusions. 9 The purpose of this clinical report is to summarize the existing evidence for the use of iNO in preterm infants and provide guidance regarding its use in this population.…”
Section: Introductionmentioning
confidence: 72%
“…8 A retrospective economic evaluation using patient-level data from the NOCLD trial (the only trial showing clinical benefit) reported that the overall mean cost per infant for the initial hospitalization was similar in the treated and placebo groups; however, when iNO therapy was initiated between 7 and 14 days of age, there was a 71% probability that the treatment decreased costs and improved outcomes. 45 Cost-benefit analysis from 2 other studies failed to show any costbenefit.…”
Section: Cost-benefit Analyses Of Routine Use Of Ino In Preterm Infantsmentioning
confidence: 99%
“…The National Institutes of Health (NIH) consensus panel (2011) and the American Academy of Pediatrics (AAP) Committee on Fetus and Newborn (2014) reported that the available evidence was insufficient to recommend the routine use of iNO in premature neonates of <34 weeks' gestation who need respiratory support to prevent or ameliorate bronchopulmonary dysplasia (BPD) [8,9]. However, the NIH statement did suggest that some neonates of <34 weeks' gestation, such as those with PH, may benefit from iNO.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of definitive evidence from randomized clinical studies regarding the benefits associated with the use of iNO in preterm neonates with HRF and PH, and the variability across published consensus guidelines regarding the use of iNO in this setting [8][9][10], assessment of a large observational data set could provide support for the clinical community in their need to define whether iNO should be utilized in their preterm neonatal patients. The observational Japanese registry evaluated in this report represents the largest data set currently available regarding the use of iNO in premature neonates with HRF and PH.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, los estudios controlados aleatorizados reunidos en un metaanálisis Cochrane reciente, con más de 3000 prematuros enrolados en más de 12 estudios, no lograron demostrar disminución del riesgo de displasia broncopulmonar. Actualmente, las indicaciones para iNO son más bien terapéuticas y reservadas para crisis de hipertensión pulmonar en dosis de 5-20 ppm en pacientes seleccionados, siguiendo así lo propuesto en el consenso del NIH 2011 16,17,18 . En la búsqueda de otras opciones para intervenir la vía alterada de NO y poder aumentar su disponibilidad, han aparecido estudios respecto a la suplementación con L-arginina y L-citrulina, siendo esta segunda la más prometedora ya que se han reportado efectos adversos en los ensayos clínicos con L-arginina.…”
Section: Prevención Con Inounclassified